Réponses

2014-04-09T22:06:16+02:00
Bonsoir,

Pour le B, nous utiliserons la formule (a - b)² = a² - 2ab + b²

B=(3\sqrt{5}-4\sqrt{11})^2\\\\B=(3\sqrt{5})^2-2\times3\sqrt{5}\times4\sqrt{11}+(4\sqrt{11})^2\\\\B=3^2(\sqrt{5})^2-24\times\sqrt{55}+4^2(\sqrt{11})^2\\\\B=9\times5-24\sqrt{55}+16\times11\\\\B=45-24\sqrt{55}+176\\\\B=221-24\sqrt{55}

Pour le C, nous utiliserons la formule : (a - b)(a + b) = a² - b²

C=(3\sqrt{2}-5\sqrt{3})(3\sqrt{2}+5\sqrt{3})\\\\C=(3\sqrt{2})^2-(5\sqrt{3})^2\\\\C=3^2(\sqrt{2})^2-5^2(\sqrt{3})^2\\\\C=9\times2-25\times3\\\\C=18-75\\\\C=-57